Medicinal Perspective of Indole Derivatives: Recent Developments and Structure-Activity Relationship Studies - Kumar, Devendra; Sharma, Sahil; Kalra, Sourav; Singh, Gurpreet; Monga, Vikramdeep; Kumar, Bhupinder (Current Drug Targets, 2020)
Heterocyclic compounds play a significant role in various biological processes of the human body and many of them are in clinical use due to their diverse, chemical and biological properties. Among these, indole is one of the most promising pharmacologically active molecules. Due to its chemical reactivity, indole has been willingly modified to obtain a variety of new lead molecules, which has been successfully utilized to obtained novel drug candidates for the treatment of different pharmacological diseases. Indole-based compounds such as vincristine (anticancer), reserpine (antihypertensive), amedalin (antidepressant) and many more describe the medicinal and pharmacological importance of the indole in uplifting human life. In this review, we compiled various reports on indole derivatives and their biological significance, including antifungal, antiprotozoal, antiplatelet, anti- Alzheimer’s, anti-Parkinson's, antioxidant and anticancer potential from 2015 onwards. In addition, structure-activity relationship studies of the different derivatives have been included. We have also discussed novel synthetic strategies developed during this period for the synthesis of different indole derivatives. We believe that this review article will provide comprehensive knowledge about the medicinal importance of indoles and will help in the design and synthesis of novel indole-based molecules with high potency and efficacy.
Keywords: synthetic strategies